Molecular cloning of a cDNA for the chicken progesterone receptor B antigen. - Zarucki-Schulz, T (Proc Natl Acad Sci U S A, 1984)
A cDNA for the chicken progesterone receptor B subunit antigen (Mr, 108,000) has been isolated from a cDNA library prepared from size-selected chicken oviduct poly(A)+RNA. A specific monoclonal antibody raised against hen progesterone receptor B subunit (alpha PR-B) was used to screen the library. Recombinant clones reacting with the antibody by virtue of antigen expression were used in hybrid-selected translation. A single clone, pPRB-1, hybridized specifically to a mRNA that yielded a Mr 108,000 protein when translated in vitro and which was immunoprecipitable by the alpha PR-B antibody. This cDNA represents a 470-base-pair portion of the PR-B nucleotide sequence. Additional clones have been subsequently isolated from the recombinant library using the insert from pPRB-1 as a specific probe. A mRNA size of approximately 3000 nucleotides was determined for the chicken progesterone receptor B subunit by formaldehyde/agarose gel electrophoresis and blot hybridization using pPRB-1 as a probe. Preliminary studies show that withdrawal of hormone from chickens treated chronically with estrogen leads to a dramatic decrease in the cellular RNA concentration of receptor B, indicating that target tissue levels of receptor B RNA are under hormonal control. IMAGES: